Dolus eventualis and its demarcation from conscious negligence - Marković Ivana (Anali Pravnog Fakulteta u Beogradu, 2023)
The aim of the paper is to determine the content of dolus eventualis in order to demarcate it from conscious negligence as the less serious form of guilt. The main challenge in Serbian law for their differentiation is their identical element of consciousness (awareness of the possibility to commit the act), while the element of will is different ("consent" to dolus eventualis and reckless assumption that the consequence of the act would not occur or that the perpetrator would be able to hinder it for conscious negligence). Firstly, various doctrines (cognitive theories, voluntative theories, and theories of risk) are analyzed. After that, the most important, typical interpretations from the Serbian jurisprudence are presented and commented on, after which it is assessed whether any of the analyzed theories could apply to Serbian Law. Finally, a more precise interpretation of the term "consent" and related questions is proposed.